DEVELOPMENT OF INNOVATIVE ENTREPRENEURSHIP - Shodiyev Bekzod Tulkinovich; Meyliyeva Guzal Sohib qizi (Ecominds Press, 2025)
This article examines the concept of innovative entrepreneurship, its main characteristics and importance in economic processes. It also analyzes the application of innovative technologies in the field of entrepreneurship, their role in increasing economic efficiency and competitiveness.
Keywords: Innovative entrepreneurship, economic development, technological innovations, sources of financing, competitiveness, innovative projects, entrepreneurial activity.